The Role of Environment on the Formation of Different FR Type Extragalactic Radio Sources - Andreasyan, R. R.; Paronyan, G. M.; Sukiasyan, A. G.
We study the environment of nearby extragalactic radio sources of different morphological type from our sample. We chose 30 3C radio galaxies of different FR class for which we have several observational dates on wavelength from radio to X ray. For the study we select the regions with radius of 500 pc around of the parent galaxy of radio sources. We bring the optical maps of these regions that are overlaid on the radio maps and maps in all available wavelength. The preliminary review show that there are some differences in the neighboring regions around radio galaxies of different FR classes.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture